Konstruksi women empowerment dalam film Memoria - Sari, Nita Puspita; Rusdiarti , Suma Riella (Universitas Mulawarman, 2024)
Women empowerment is a form of women's resistance to the domination of power and gender-based violence. This research aims to reveal the construction of women empowerment in the film Memoria (2016) by Kamila Andini through analysis of the film's narrative structure and cinematographic elements. The identification of the film's narrative structure uses Gérard Genette's narratology theory through the concept of focalization and the identification of cinematographic aspects using Metz semiotics. The method used in the research is the descriptive qualitative method. Data collection techniques were carried out by reviewing film sequences, literature studies, and identifying cinematographic aspects. The results show that Maria's focalization dominates the story, moves the story, and there are six grand syntagmas, namely descriptive syntagma, parallel syntagma, bracket syntagma, scene, episodic sequence, and insert subjective. Analyzing the narrative structure and the cinematographic aspects of the film through a series of syntagms, both represent the construction of women empowerment continuously. Maria is a woman who survives various life challenges and can heal the trauma within herself. The healing process starts from within oneself (self-healing) and then sharing stories (sharing) with family or trusted people. These things are steps toward freedom, justice, and women empowerment.